Preservation of Bioactive Compounds and Quality Parameters of Watermelon Juice Enriched with L-Citrulline through Short Thermal Treatment - Martha P. Tarazona-Díaz; Ascensión Martínez-Sánchez; Encarna Aguayo (Journal of Food Quality)
L-citrulline is a nonessential amino acid with demonstrated health benefits for humans, and watermelon is a fruit rich in this amino acid. The juice industry is developing functional beverages through the enrichment with external bioactive compounds; this kind of industry uses conventional pasteurization because of its efficiency and simplicity. In this experiment, the effects of pasteurization (80°C for 40 s or 90 s) and storage (4°C for 30 days) on different parameters were evaluated in a watermelon juice (3.68 g kg−1 of natural L-citrulline) enriched with external L-citrulline (12 g kg−1). Enzymatic activity (peroxidase, pectin methyl esterase, and polygalacturonase) was inactivated (74 to 89%, 89 to 90%, and 11 to 15%, resp.) with the pasteurization treatment, obtaining the highest degradation with the longest heating time. According to the rheology study, the juice’s elasticity was mainly affected by type of heat treatment while its viscosity was more stable and affected by storage time. A reduction in bioactive compounds content, around 10–16% for lycopene and 19–20% for L-citrulline, was observed after the pasteurization treatments, with a higher decrease with increased treatment time. Storage time also induced a reduction in lycopene and L-citrulline. The shelf life was limited by sensorial parameters.